Cardiac imaging to detect coronary artery disease in athletes aged 35 years and older. A scoping review. (21st September 2017) - Braber, T. L.; Reitsma, J. B.; Mosterd, A.; Willemink, M. J.; Prakken, N. H. J.; Halle, M.; Sharma, S.; Velthuis, B. K.
Abstract : Sudden cardiac death (SCD) is a devastating event in athletes. Screening efforts that were first directed at athletes younger than 35 years are now focusing on the rapidly growing group of older sportspersons. Athletes aged ≥35 years have a 10‐fold increased risk of exercise‐related cardiac arrest, mostly due to coronary artery disease (CAD). Although cardiac imaging is pivotal in identifying CAD, the role of imaging modalities in screening asymptomatic older sportspersons remains unclear. We performed a scoping review to identify the role of cardiac imaging to detect CAD in older sportspersons and to identify gaps in the existing literature. We searched MEDLINE, EMBASE and the Cochrane library for studies reporting data on cardiac imaging of CAD in sportspersons ≥35 years. The systematic search yielded 1737 articles, and 14 were included in this scoping review. Imaging modalities included two echocardiography, one unenhanced computed tomography (CT) for coronary artery calcium scoring (CACS), three CACS and contrast‐enhanced CT angiography (CCTA), two CACS and cardiac magnetic resonance (CMR), one CCTA with CMR and echocardiography, two CCTA, two CMR, and one myocardial perfusion imaging article. The low number of relevant articles and the selection bias introduced by studying specific groups, like veteran marathon runners, indicate the need for future research. Cardiac CT (CACS and CCTA) probably has the highest potential for pre‐participation screening, with high diagnostic value to detect CAD and low radiation dose. However, currently there is insufficient evidence for incorporating routine cardiac imaging in the pre‐participation screening of asymptomatic sportspersons over 35 years.